2018
DOI: 10.21315/aamj2018.23.2.7
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Relationship Between Materialism and Conspicuous Consumption: Validation in the Indian Context

Abstract: With urbanisation and increase in per capita income, there has been an astonishing rise in material-oriented tendencies in the Indian population. This study aims to examine the significance of material-centric behaviour of women in today's growing consumer societies. Using structural equation modelling, the paper proposes a model depicting the relationship between materialism and conspicuous consumption among Indian women consumers. Though all the three factors, namely success, centrality, and happiness, contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Traditional research has demonstrated that materialism is deeply related to conspicuous consumption, suggesting that consumers with a high materialism tend to spend more ostentatiously on expensive fashion products than those with low materialism (Wu et al , 2017; Lewis and Moital, 2016). Similarly, Chacko et al (2018) examine positive relationship between materialism and conspicuous consumption. Meanwhile, Siahtiri and Lee (2019) demonstrate that materialistic perception is closely related to high brand prominence.…”
Section: Theoretical Framework and Hypothesismentioning
confidence: 99%
“…Traditional research has demonstrated that materialism is deeply related to conspicuous consumption, suggesting that consumers with a high materialism tend to spend more ostentatiously on expensive fashion products than those with low materialism (Wu et al , 2017; Lewis and Moital, 2016). Similarly, Chacko et al (2018) examine positive relationship between materialism and conspicuous consumption. Meanwhile, Siahtiri and Lee (2019) demonstrate that materialistic perception is closely related to high brand prominence.…”
Section: Theoretical Framework and Hypothesismentioning
confidence: 99%
“…Goods purchased through conspicuous consumption are often expensive, fashionable, or scarce. Numerous studies have shown that materialistic goals are associated with a preference for conspicuous consumption (Chacko et al, 2018;Podoshen & Andrzejewski, 2012). One example of a materialistic goal is 'image' (Kasser & Ryan, 1996).…”
Section: Theory Developmentmentioning
confidence: 99%
“…Several studies have examined conspicuous motivation in relation to socio-demographic variables, such as age and gender (e.g., Amatulli, Guido, & Nataraajan, 2015; O’Cass & McEwen, 2004; Roux, Tafani, & Vigneron, 2017), and psychological conditions such as self-concept and tendency to materialism (e.g., Chacko, Prashar, & Ramanathan, 2018; Podoshen & Andrzejewski, 2012; Truong & McColl, 2011). Studies have found that men show a greater tendency than women to consume luxury goods due to conspicuous motivation (Kamineni, 2005; O’cass & McEwen, 2004) and search for social acceptance through product exposure (Tse, Belk, & Zhou, 1989).…”
Section: Introductionmentioning
confidence: 99%